Could HPV-DNA Test Solve the Dilemma About Sentinel Node Frozen Section Accuracy in Early Stage Cervical Cancer? Hypothesis and Rationale. (28th May 2014) - Noventa, Marco; Ancona, Emanuele; Saccardi, Carlo; Litta, Pietro; D'Antona, Donato; Nardelli, Giovanni Battista; Gizzo, Salvatore
<x xml:space="preserve">Abstract</x> In order to reduce the surgical invasiveness in early-stage cervical-cancer treatment, the sentinel lymph-node (SLN) technique could be considered as a possible intraoperative-guidance to lymphadenectomy decision making. Unfortunately its accuracy ranges between 33.3% and 100% in different studies. Recent manuscripts suggest that HPV-DNA presence in pelvic-lymph-nodes may represent a molecular marker of micrometastases. According to this hypothesis, the rationale in proposing the HPV-DNA-test when negative frozen-section occurs is due to the expected improvement of its diagnostic-accuracy. HPV-DNA test may represent a marker able to discriminate at frozen section the false-negative from the truth-negative tests filling the gap between optimal and real frozen-section accuracy.